2021
DOI: 10.18488/journal.1.2021.118.376.387
|View full text |Cite
|
Sign up to set email alerts
|

Balancing Negative and Positive Factors in Foreign Language Learning

Abstract: The reasons why people study foreign languages vary tremendously. Some are intrinsically, while others depended on extrinsic reward to begin their study. Past studies have shown that foreign language learners have display different types of fear throughout the learning process. Nevertheless, sometimes, the negative factors that cause their fear can sometimes be overcome by the positive factors that made them stayed on to the classes. This study is done to investigate the balance between the negative and positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…This research also shows that fear of negative evaluation is the prime cause of anxiety among respondents. Past studies by Rahmat (2020) and Boon (2021) demonstrate the same findings as well.…”
Section: Anxietysupporting
confidence: 71%
See 1 more Smart Citation
“…This research also shows that fear of negative evaluation is the prime cause of anxiety among respondents. Past studies by Rahmat (2020) and Boon (2021) demonstrate the same findings as well.…”
Section: Anxietysupporting
confidence: 71%
“…In the past years numerous researches have been done in looking into foreign language anxiety amongst learners, most of which has indicated that anxiety has a negative or weakening effect on language learning. Findings from previous studies point to a significant correlation between communication apprehension, fear of negative evaluation and test anxiety to foreign language anxiety, (Ismail et al, 2022); Darmawangsa et al, 2020;Boon et al, 2021). Furthermore, the study by (Rahmat 2019) reported that fear in language learning is a cycle.…”
Section: Statement Of Problemmentioning
confidence: 89%
“…Learners depend on different factors of motivation to make them pursue the learning task further. This motivation pushes the learners to be satisfied with the learning task (Rahmat, 2021). Motivate learners display confidence in learning.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…The significance of studying a foreign language has been mentioned in the Malaysian Education Blueprint 2015-2025, which has also been acknowledged as one of the key components in realizing the country's vision of being a fully developed nation. A foreign language is defined as a language spoken by people who speak other than their native language (Boon et al, 2021). Many universities have considered foreign language courses, such as Mandarin, Arabic, French, Korean, and Japanese, a graduation requirement.…”
Section: Background Of Studymentioning
confidence: 99%
“…According to Djafri and Wimbarti (2018), Japanese learners have the highest level of foreign language anxiety, followed by learners of Arabic, French, Korean, and English. Boon et al (2021) discovered that despite obstacles such as the fear of "negative evaluation" and "tests", learners' internal positive motivation plays a crucial role in keeping them engaged in their Japanese language learning journey. Ibrahim et al (2023) applied Herzberg's Two-Factor Theory to identify students' motivations, while Fu (2010) examined factors influencing student satisfaction across different higher education settings, including face-to-face, webbased, and blended classrooms.…”
Section: Statement Of Problemmentioning
confidence: 99%